Use of mindfulness, meditation and relaxation to treat vasomotor symptoms. (4th March 2017) - Goldstein, K. M.; Shepherd-Banigan, M.; Coeytaux, R. R.; McDuffie, J. R.; Adam, S.; Befus, D.; Goode, A. P.; Kosinski, A. S.; Masilamani, V.; Williams, J. W.
Abstract: Postmenopausal women with bothersome vasomotor symptoms (VMS) often seek alternatives to hormone-based treatment due to medication risks or personal preference. We sought to identify the effects of meditation, mindfulness, hypnosis and relaxation on VMS and health-related quality of life in perimenopausal and postmenopausal women. To do this, we conducted an umbrella review supplemented by new randomized, controlled trials (RCTs) published since the most recent good-quality systematic review for eligible interventions. We searched MEDLINE and the Cochrane Database of Systematic Reviews, PubMed, EMBASE, CINAHL and the Allied and Complementary Medicine Databases. We identified five systematic reviews and six new RCTs that met eligibility criteria. In a new meta-analysis examining four RCTs comparing paced respiration with a control group, we found that paced respiration is not associated with a statistically significant decrease in VMS frequency (standardized mean difference (SMD) 0.04, 95% confidence interval (CI) -0.73 to 0.82, I 2  =   56.6%, three trials) or severity (SMD 0.06, 95% CI -0.69 to 0.80; I 2  =   65.1%, three trials). There was not sufficient new information to conduct meta-analyses that examined the effect of mindfulness or hypnosis on our outcomes of interest. No effect on VMS or quality of life was found between various relaxation or mindfulness interventions.